THE HISTORICAL DEVELOPMENT OF FRENCH FOLK SONGS AND THEIR CULTURAL FOUNDATIONS (Ideal Journal of Multidisciplinary Research, 2026)
This article is devoted to the study of the history of the formation and the cultural foundations of French folk songs. The work highlights the origin of folk songs, their development during different historical periods, their regional and social characteristics, as well as their influence on national culture. The article analyzes the genres of folk songs, their rhythmic and melodic features, their connection with religious and secular musical traditions, and the musical reflection of the life and values of the people. It also shows the significance of French musical heritage and folk creativity in modern cultural development.
Keywords: folk songs, lyric poetry, music, folklore, traditions, rhythm, poetry, troubadours, trouvères.